Impact-resistant and wear-resistant self-lubricating material, composite plate and preparation method thereof based on polyketone
By modifying polyketone materials, adding acid anhydride graft modified polyethylene, glass fiber, inorganic filler and lubricant, it forms an impact-resistant and wear-resistant self-lubricating material, which solves the wear resistance of polymer-based wear-resistant composite materials under high requirements Performance issues achieve better friction reduction and wear resistance, and are suitable for a variety of friction and wear conditions.
Patent Information
- Application Number
- CN201910149510.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-02-28
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2039-02-28
AI Technical Summary
Polymer-based wear-resistant composite materials are difficult to meet wear resistance under high customer design requirements and working conditions. In particular, the high friction factor of POK materials limits its application in the field of friction and wear.
By modifying the polyketone material, adding acid anhydride graft modified polyethylene, glass fiber, inorganic filler, lubricant and antioxidant, it forms an impact-resistant and wear-resistant self-lubricating material based on polyketone, combining vacuum sintering and extrusion granulation processes. , improve the friction reduction and wear resistance of the material.
It reduces the friction factor of polyketone materials, expands its application range in the field of friction and wear, improves the wear resistance and friction reduction performance of composite panels, and meets the requirements of various friction and wear conditions.
Smart Images

Figure CN109910399B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wear-resistant plates, in particular to an impact-resistant and wear-resistant self-lubricating material and a composite plate based on polyketone and a preparation method thereof. Background Art
[0002] Through special modification, polymer-based wear-resistant composite materials are widely used in the field of friction materials due to their excellent friction reduction and wear resistance. They also have excellent properties such as shock absorption, low noise, light weight, and easy processing. In particular, they can easily form a stable transfer film with the wear parts during use, thereby further improving the lubrication effect.
[0003] With the widespread application of polymer-based wear-resistant composite materials, customer design requirements and working conditions requirements are becoming increasingly higher, especially for the wear resistance of materials, which the currently commonly used polymer-based composite materials are difficult to meet.
[0004] POK is a new type of green and environmentally friendly polymer, which is polymerized from carbon monoxide and olefins. It is currently the only semi-crystalline engineering plastic with carbon atoms in the main chain. It has high crystallinity and compact crystal structure. Its special structure makes POK have excellent wear resistance. However, when used alone, the friction coefficient is too high, which limits its application in the field of friction and wear. Summary of the invention
[0005] In view of this, the present invention reduces the friction factor of the material through modification, thereby improving the friction reduction performance of POK and giving full play to its excellent wear resistance, so as to provide an impact-resistant and wear-resistant self-lubricating material, composite plate and preparation method thereof based on polyketone to solve the above problems.
[0006] The invention discloses an impact-resistant and wear-resistant self-lubricating material based on polyketone, which is composed of polyketone, anhydride grafted modified polyethylene, glass fiber, inorganic filler, lubricant, and antioxidant. The weight percentage of the polyketone is 45%-79.8%, the weight percentage of the anhydride grafted modified polyethylene is 5%-15%, the weight percentage of the glass fiber is 5%-20%, the weight percentage of the inorganic filler is 5%-15%, the weight percentage of the lubricant is 0.1-5%, and the weight percentage of the antioxidant is 0.1%-3%. The anhydride grafted modified polyethylene is grafted and modified by anhydride accounting for 1%-5% of the total amount of polyethylene. After vacuum sintering treatment of glass fiber and inorganic filler, they are mixed with polyketone, anhydride grafted modified polyethylene and lubricant to obtain the impact-resistant and wear-resistant self-lubricating material based on polyketone.
[0007] Furthermore, the inorganic filler is one or more of barium sulfate or calcium carbonate, and its mesh size is greater than 500 meshes.
[0008] Furthermore, the acid anhydride is maleic anhydride.
[0009] Furthermore, the lubricant is one or more of polytetrafluoroethylene, colloidal graphite, and molybdenum disulfide, wherein the mesh number of polytetrafluoroethylene is greater than 300 meshes, the mesh number of colloidal graphite is greater than 1000 meshes, and the mesh number of molybdenum disulfide is greater than 300 meshes.
[0010] Furthermore, the antioxidant is one or more of triester phosphite, pentaerythritol ester, and triphenyl phosphite.
[0011] Furthermore, the aspect ratio of the glass fiber is 8-12.
[0012] A composite plate includes a substrate, a sintered layer sintered on the substrate, and an impact-resistant, wear-resistant, self-lubricating layer disposed on the sintered layer. The impact-resistant, wear-resistant, self-lubricating layer is made of an impact-resistant, wear-resistant, self-lubricating material based on polyketone. The impact-resistant, wear-resistant, self-lubricating material based on polyketone consists of polyketone, anhydride grafted modified polyethylene, glass fiber, inorganic filler, and antioxidant. The weight percentage of the polyketone is 45%-79.8%, the weight percentage of the anhydride grafted modified polyethylene is 5%-15%, the weight percentage of the glass fiber is 5%-20%, the weight percentage of the inorganic filler is 5%-15%, the weight percentage of the lubricant is 0.1%-5%, and the weight percentage of the antioxidant is 0.1%-3%. After the glass fiber and the inorganic filler are vacuum sintered and mixed with the polyketone, the anhydride grafted modified polyethylene, and the lubricant, the sintered layer has a plurality of pores of arbitrary shapes penetrating the sintered layer, and the pores account for 15-25%.
[0013] Furthermore, the substrate is one of a copper plate, a steel plate, a stainless steel plate and an aluminum plate.
[0014] A method for preparing a composite plate comprises the following steps:
[0015] S1: providing an impact-resistant and wear-resistant self-lubricating material based on polyketone, the impact-resistant and wear-resistant self-lubricating material based on polyketone is composed of polyketone, anhydride grafted modified polyethylene, glass fiber, inorganic filler, and antioxidant, the weight percentage of the polyketone is 45%-79.8%, the weight percentage of the anhydride grafted modified polyethylene is 5%-15%, the weight percentage of the glass fiber is 5%-20%, the weight percentage of the inorganic filler is 5%-15%, the weight percentage of the lubricant is 0.1%-5%, the weight percentage of the antioxidant is 0.1%-3%, and the anhydride grafted modified polyethylene is grafted and modified by anhydride accounting for 1%-5% of the total amount of polyethylene;
[0016] S2: vacuum sintering the glass fiber and the inorganic filler, maintaining the vacuum degree at -0.1 MPa to -0.15 MPa, and the sintering temperature at 350 to 450 degrees;
[0017] S3: Mixing the vacuum sintered glass fiber and inorganic filler with the polyketone, anhydride grafted modified polyethylene, lubricant and antioxidant, and extruding and granulating to form composite particles at an extrusion temperature of 210 to 240 degrees.
[0018] S4: providing a substrate and copper alloy powder;
[0019] S5: sintering the copper alloy powder and rolling to form a sintered layer on a substrate, wherein the sintered layer has a plurality of pores of any shape penetrating the sintered layer, and the pores account for 15-25%;
[0020] S6: laying the composite particles formed in step S3 on the sintered layer, heating and rolling, and controlling the rolling temperature to be above 150 to 170 degrees to form the impact-resistant, wear-resistant and self-lubricating composite plate.
[0021] Furthermore, after step S2 and before step S3, the method further includes the step of pretreating the vacuum sintered glass fibers and inorganic fillers, that is, mixing the vacuum sintered glass fibers and inorganic fillers with an organic solvent, and drying the mixed glass fibers and inorganic fillers.
[0022] Compared with the prior art, the impact-resistant and wear-resistant self-lubricating material based on polyketone provided by the present invention uses the polyketone, and anhydride-grafted modified polyethylene, glass fiber, inorganic filler, lubricant and antioxidant are added to the polyketone. In addition, the glass fiber and the inorganic filler are first sintered during mixing to improve the fusion degree and cleanliness of the glass fiber and the inorganic filler. The modified polyethylene grafted with anhydride can improve the mixing uniformity and dispersibility of various additives in the polyketone due to its special grafted block structure. Under the coordination of their respective contents and mesh sizes, the wear resistance of the polyketone can be fully utilized, and the friction coefficient of the polyketone when used alone is also reduced, thereby increasing the scope of use of the polyketone material, that is, the friction reduction performance of the polyketone is improved, and its excellent wear resistance is fully utilized, so as to obtain a self-lubricating composite plate with better performance that meets various friction and wear working conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The present invention provides a flow chart of a method for preparing a composite plate.
[0024] Figure 2 for Figure 1 Schematic diagram of the structure of the composite plate prepared by the preparation method. DETAILED DESCRIPTION
[0025] The specific embodiments of the present invention are further described in detail below. It should be understood that the description of the embodiments of the present invention herein is not intended to limit the protection scope of the present invention.
[0026] The impact-resistant and wear-resistant self-lubricating material based on polyketone provided by the present invention is composed of polyketone, anhydride grafted modified polyethylene, glass fiber, inorganic filler, lubricant and antioxidant. Specifically, the weight percentage of the polyketone is 45%-79.8%, the weight percentage of the anhydride grafted modified polyethylene is 5%-15%, the weight percentage of the glass fiber is 5%-20%, the weight percentage of the inorganic filler is 5%-15%, the weight percentage of the lubricant is 0.1%-5%, and the weight percentage of the antioxidant is 0.1%-3%. The polyketone is a new type of green and environmentally friendly polymer, which is polymerized by carbon monoxide and olefins. Polyketone is the only semi-crystalline engineering plastic with carbon atoms on the main chain among current polymer materials, with high crystallinity and compact crystal structure, so the polyketone has very excellent wear resistance. However, when it is used alone, the friction coefficient is too high, which limits its application in the field of friction and wear, so it needs to be modified. Therefore, in the field of wear-resistant self-lubrication, it is also necessary to modify it in order to meet the requirements of wear-resistant self-lubrication of skateboards or sliding bearings. As we all know, for skateboards or sliding bearings, the wear resistance is one of the most important parameters, which determines the life of the skateboard or sliding bearing. The use of the polyketone as the matrix material has better wear resistance due to its special crystal structure. The anhydride grafted modified polyethylene is formed by grafting several anhydride molecules on the polyethylene molecular chain by means of chemical reaction to form a new substance. When the polyethylene is modified, anhydride accounting for 1% to 5% of the total mass of the polyethylene is used for modification, and the anhydride can be maleic anhydride.
[0027] Adding polyethylene that has been modified by anhydride grafting will cause changes in the microscopic morphology of polyketone and its additives. Specifically, the particle size distribution range of the polyethylene phase will become smaller, its particle size will also become smaller, the interface distinction between the polyethylene phase and the polyketone phase will become more blurred, and the adhesion between the two phases will be significantly enhanced. Other additives, especially polytetrafluoroethylene, graphite, molybdenum disulfide, etc. in the lubricant, can be observed to have significantly improved agglomeration under microscopic morphological observation, which shows that the dispersion uniformity of the material can be better improved after anhydride grafting modification.
[0028] In the present invention, the anhydride grafted modified polyethylene has very good dispersion uniformity. It is usually used as an additive for thermoplastic material modification. By controlling its addition amount, the overall mixing uniformity of the material is improved, so that the performance consistency and stability of the skateboard or sliding bearing are achieved. The aspect ratio of the glass fiber is 8 to 10. In the present embodiment, the aspect ratio of the glass fiber is 8. Glass fiber is used as a reinforcing material in the present invention, which is used to improve the bearing capacity and compression resistance of the material after molding, and also has a gain effect on wear resistance. In the present invention, in order to improve the bearing capacity and compression resistance of the material after molding, glass fibers with a smaller aspect ratio are added. The inorganic filler can be one or more of barium sulfate or calcium carbonate, and its mesh number is greater than 500 meshes. In the manufacturing process, the inorganic filler must first be mixed with the glass fiber. At the same time, in order to further improve the cleanliness, bearing capacity and compression resistance of the inorganic filler after mixing with the glass fiber, the inorganic filler and the glass fiber need to be sintered first, that is, the polyketone, the grafted modified polyethylene, the lubricant and the mixture of the sintered inorganic filler and the glass fiber are mixed. The inorganic filler can be barium sulfate and calcium carbonate, and its main purpose is to improve the bearing capacity of the material and reduce the cost. Its mesh number is a particle size of more than 500 meshes, so that it can obtain better dispersibility and uniformity with the glass fiber during the blending process. The mesh number of the inorganic filler is determined by the aspect ratio of the glass fiber. In the present invention, since the aspect ratio of the glass fiber is 8 to 10, the mesh number of the inorganic filler must be greater than 500 meshes to obtain the required dispersibility and uniformity. The lubricant can be one or more of polytetrafluoroethylene, colloidal graphite, and molybdenum disulfide, which are used to reduce the friction coefficient of the material and improve the friction reduction performance of the material. The antioxidant can be one or more of phosphite triester, pentaerythritol ester, and triphenyl phosphite, which are used to improve the antioxidant ability of the material, improve the processing performance of the material, and avoid defects such as color difference and pits. In the present invention, since the base material uses polyketone and anhydride grafted modified polyethylene, it is necessary to select pentaerythritol ester as an antioxidant to avoid interference with the properties of the polyketone and anhydride grafted modified polyethylene.
[0029] like Figure 1 As shown, it is a flow chart of a method for preparing a composite board using a polyketone-based impact-resistant, wear-resistant, self-lubricating material. The method for preparing the composite board comprises the following steps:
[0030] S1: providing an impact-resistant and wear-resistant self-lubricating material based on polyketone, wherein the impact-resistant and wear-resistant self-lubricating material based on polyketone is composed of polyketone, anhydride grafted modified polyethylene, glass fiber, inorganic filler, lubricant and antioxidant;
[0031] S2: vacuum sintering the glass fiber and the inorganic filler, maintaining the vacuum degree at -0.1 MPa to -0.15 MPa, and the sintering temperature at 350 to 450 degrees;
[0032] S3: Mixing the vacuum sintered glass fiber and inorganic filler with the polyketone, anhydride grafted modified polyethylene, lubricant and antioxidant, and extruding and granulating to form composite particles at an extrusion temperature of 210 to 240 degrees.
[0033] S4: providing a substrate and copper alloy powder;
[0034] S5: sintering and rolling the copper alloy powder to form a sintered layer on a substrate, wherein the sintered layer has a plurality of regular or irregular pores penetrating the sintered layer, and the pores account for 15-25%;
[0035] S6: laying the composite particles formed in step S3 on the sintered layer, heating and rolling, and controlling the rolling temperature to be above 150 to 170 degrees to form the impact-resistant, wear-resistant and self-lubricating composite plate.
[0036] After step S2, the vacuum-sintered glass fibers and inorganic fillers should be pretreated, that is, the vacuum-sintered glass fibers and inorganic fillers are mixed with an organic solvent and dried after mixing.
[0037] Through the above steps, the impact-resistant and wear-resistant self-lubricating composite plate is prepared. Figure 2As shown. The wear-resistant and anti-bite composite plate includes a substrate 10, a sintered layer 11 arranged on the substrate 10, and an impact-resistant, wear-resistant and self-lubricating composite layer 12 rolled on the sintered layer 11. The substrate 10 is a copper plate, a steel plate, a carbon steel plate, a stainless steel plate, and an aluminum plate. In the present embodiment, the substrate 10 is a steel plate, and its thickness can be determined according to actual needs. The sintered layer 11 is made of a copper alloy material. When the copper alloy is sintered, a plurality of pores of arbitrary shapes penetrating the sintered layer will be formed on the sintered layer 11, and the pores are used to fill the impact-resistant, wear-resistant and self-lubricating material based on polyketone to improve the impact resistance of the impact-resistant, wear-resistant and self-lubricating composite layer 12. The plurality of pores of arbitrary shapes or regular or irregular shapes penetrate the sintered layer 11, so that the impact-resistant, wear-resistant and self-lubricating material can be more sandwiched or filled in the pores to further improve the life of the composite plate. At the same time, since the pores run through the sintered layer 11, it is beneficial to increase the friction between the substrate and the sintered layer 11 during the rolling process, thereby improving the bonding strength between the substrate and the sintered layer 11. The impact-resistant, wear-resistant and self-lubricating composite layer 12 is made of an impact-resistant, wear-resistant and self-lubricating material based on polyketone. The impact-resistant, wear-resistant and self-lubricating material based on polyketone is composed of polyketone, anhydride grafted modified polyethylene, glass fiber, inorganic filler, lubricant and antioxidant. Specifically, the weight percentage of the polyketone is 45%-79.8%, the weight percentage of the anhydride grafted modified polyethylene is 5% to 15%, the weight percentage of the glass fiber is 5% to 20%, the weight percentage of the inorganic filler is 5% to 15%, the weight percentage of the lubricant is 0.1%-5%, and the weight percentage of the antioxidant is 0.1% to 3%. Specific embodiments:
[0038] Table 1 Example data table
[0039]
[0040] Embodiment 1:
[0041] Step 1: Weigh 58.5 parts of polyketone, 12 parts of polyethylene with a maleic anhydride grafting ratio of 3%, 18 parts of sintered glass fiber, 10 parts of barium sulfate, and 1.5 parts of polytetrafluoroethylene.
[0042] Step 2: Add all the above raw materials into a high-speed mixer at a rotation speed of 350 rpm and mix for 20 minutes to obtain a mixture.
[0043] Step 3: The mixed material is extruded into granules through a twin-screw extruder at an extrusion temperature of 230 degrees.
[0044] Step 4: The obtained particles are spread on the surface of the plate for melt sintering and composite processing is performed by hot rolling to obtain a three-layer composite plate with good wear resistance.
[0045] Embodiment 2:
[0046] Step 1: Weigh 69.5 parts of polyketone, 12 parts of polyethylene with a maleic anhydride grafting ratio of 3%, 13 parts of sintered glass fiber, 5 parts of barium sulfate, and 0.5 parts of polytetrafluoroethylene.
[0047] Step 2: Add all the above raw materials into a high-speed mixer at a rotation speed of 350 rpm and mix for 20 minutes to obtain a mixture.
[0048] Step 3: The mixed material is extruded into granules through a twin-screw extruder at an extrusion temperature of 220 degrees.
[0049] Step 4: The obtained particles are spread on the surface of the plate for melt sintering and composite processing is performed by hot rolling to obtain a three-layer composite plate with good wear resistance.
[0050] Comparative Example 1:
[0051] Step 1: Weigh 100 parts of polyketone.
[0052] Step 2: Add all the above raw materials into a high-speed mixer at a rotation speed of 350 rpm and mix for 20 minutes to obtain a mixture.
[0053] Step 3: The mixed material is extruded into granules through a twin-screw extruder at an extrusion temperature of 210 degrees.
[0054] Step 4: The obtained particles are spread on the surface of the plate for melt sintering and composite processing is performed by hot rolling to obtain a three-layer composite plate with good wear resistance.
[0055] Performance comparison is carried out through end face friction and wear performance experiments
[0056] The above materials were processed into plates of equal thickness, and the performance was compared and evaluated using an MMU-12 end surface testing machine. The test materials were processed into sheets of 37*37*2.0mm and tested under the following test conditions: Abrasive material: 45# steel (HRC42-47, Ra0.6-0.8)
[0057] Grinding part size: contact surface is a Φ30*Φ22 ring
[0058] Line speed: 0.5m / s
[0059] Loading load: 10MPa
[0060] Test time: 3h
[0061] Lubrication conditions: initial grease lubrication.
[0062] Finally, the test results of the embodiments and comparative examples are shown in Table 2.
[0063] Table 2
[0064] Material Name Friction factor Wear Temperature rise Example 1 0.0251 0.007mm 68.0℃ Example 2 0.0331 0.009mm 75.7℃ Comparative Example 0.0949 0.058mm 158.6℃
[0065] As can be seen from Table 2 above, the friction coefficient of POK after modification has been significantly reduced, and its performance in friction and wear performance tests is very outstanding.
[0066] Compared with the prior art, the impact-resistant and wear-resistant self-lubricating material based on polyketone provided by the present invention uses the polyketone, and anhydride grafted modified polyethylene, glass fiber, inorganic filler, lubricant and antioxidant are added to the polyketone. In addition, the glass fiber and the inorganic filler are first sintered during mixing to improve the fusion degree and cleanliness of the glass fiber and the inorganic filler. The use of anhydride grafted modified polyethylene improves the dispersion uniformity of various additives in the polyketone, and the coordination of their respective contents and mesh sizes, thereby fully utilizing the wear resistance of the polyketone, and also reducing the friction coefficient of the polyketone when used alone, thereby expanding the use range of the polyketone, that is, improving the friction reduction performance of the polyketone, giving full play to its excellent wear resistance, thereby preparing a self-lubricating composite plate with better performance and better stability.
[0067] The above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modification, equivalent substitution or improvement within the spirit of the present invention is included in the scope of the claims of the present invention.
Claims
1. Impact-resistant and wear-resistant self-lubricating material based on polyketone, characterized by: The impact-resistant and wear-resistant self-lubricating material based on polyketone is composed of polyketone, anhydride grafted modified polyethylene, glass fiber, inorganic filler, lubricant, and antioxidant. The weight percentage of the polyketone is 45%-79.8%, the weight percentage of the anhydride grafted modified polyethylene is 5%-15%, the weight percentage of the glass fiber is 5%-20%, the weight percentage of the inorganic filler is 5%-15%, the weight percentage of the lubricant is 0.1-5%, the weight percentage of the antioxidant is 0.1%-3%, the anhydride grafted modified polyethylene is grafted and modified by anhydride accounting for 1%-5% of the total amount of polyethylene, and the aspect ratio of the glass fiber is 8 To 10, the mesh number of the inorganic filler is greater than 500 meshes, the lubricant is one or more of polytetrafluoroethylene, colloidal graphite, and molybdenum disulfide, wherein the mesh number of polytetrafluoroethylene is greater than 300 meshes, the mesh number of colloidal graphite is greater than 1000 meshes, and the mesh number of molybdenum disulfide is greater than 300 meshes. After the glass fiber and the inorganic filler are vacuum sintered, they are mixed with polyketone, anhydride grafted modified polyethylene, and the lubricant to obtain the impact-resistant and wear-resistant self-lubricating material based on polyketone. The sintering temperature of the glass fiber and the inorganic filler is 350 degrees to 450 degrees. When using the impact-resistant and wear-resistant self-lubricating material based on polyketone, heating and rolling are required, and the rolling temperature is controlled at 150 degrees to 170 degrees.
2. The impact-resistant and wear-resistant self-lubricating material based on polyketone according to claim 1, characterized in that: The inorganic filler is one or more of barium sulfate and calcium carbonate.
3. The impact-resistant and wear-resistant self-lubricating material based on polyketone according to claim 1, characterized in that: The acid anhydride is maleic anhydride.
4. The impact-resistant and wear-resistant self-lubricating material based on polyketone according to claim 1, characterized in that: The antioxidant is one or more of triester phosphite, pentaerythritol ester and triphenyl phosphite.
5. A composite board, characterized in that: The composite plate includes a substrate, a sintered layer sintered on the substrate, and an impact-resistant, wear-resistant self-lubricating layer arranged on the sintered layer, wherein the impact-resistant, wear-resistant self-lubricating layer is made of an impact-resistant, wear-resistant self-lubricating material based on polyketone, and the impact-resistant, wear-resistant self-lubricating material based on polyketone is composed of polyketone, anhydride grafted modified polyethylene, glass fiber, inorganic filler, and antioxidant, the weight percentage of the polyketone is 45%-79.8%, the weight percentage of the anhydride grafted modified polyethylene is 5%-15%, the weight percentage of the glass fiber is 5%-20%, the weight percentage of the inorganic filler is 5%-15%, the weight percentage of the lubricant is 0.1%-5%, and the weight percentage of the antioxidant is 0.1%-3%. After vacuum sintering treatment of glass fiber and inorganic filler, they are mixed with polyketone, anhydride grafted modified polyethylene and lubricant. The sintering temperature of the glass fiber and inorganic filler is 350 to 450 degrees, the aspect ratio of the glass fiber is 8 to 10, the mesh number of the inorganic filler is greater than 500 meshes, and the lubricant is one or more of polytetrafluoroethylene, colloidal graphite and molybdenum disulfide, wherein the mesh number of polytetrafluoroethylene is greater than 300 meshes, the mesh number of colloidal graphite is greater than 1000 meshes, and the mesh number of molybdenum disulfide is greater than 300 meshes. When using the impact-resistant and wear-resistant self-lubricating material based on polyketone, heating and rolling are required, and the rolling temperature is controlled at 150 to 170 degrees. The sintered layer has a plurality of pores of arbitrary shapes penetrating the sintered layer, and the pores account for 15-25%.
6. The composite panel according to claim 5, characterized in that: The substrate is a copper plate, a steel plate, a stainless steel plate, or an aluminum plate.
7. A method for preparing a composite board, comprising the following steps: S1: Provide an impact-resistant and wear-resistant self-lubricating material based on polyketone, which is composed of polyketone, anhydride grafted modified polyethylene, glass fiber, inorganic filler, and antioxidant, wherein the weight percentage of the polyketone is 45%-79.8%, the weight percentage of the anhydride grafted modified polyethylene is 5%-15%, the weight percentage of the glass fiber is 5%-20%, the weight percentage of the inorganic filler is 5%-15%, and the weight percentage of the lubricant is 0 .1%-5%, the weight percentage of the antioxidant is 0.1% to 3%, the anhydride grafted modified polyethylene is grafted and modified by 1% to 5% of the anhydride of the total amount of polyethylene, the aspect ratio of the glass fiber is 8 to 10, the mesh number of the inorganic filler is greater than 500 mesh, the lubricant is one or more of polytetrafluoroethylene, colloidal graphite, and molybdenum disulfide, wherein the mesh number of polytetrafluoroethylene is greater than 300 mesh, the mesh number of colloidal graphite is greater than 1000 mesh, and the mesh number of molybdenum disulfide is greater than 300 mesh; S2: vacuum sintering the glass fiber and the inorganic filler, with the vacuum degree maintained at -0.1 MPa to -0.15 MPa and the sintering temperature at 350 to 450 degrees; S3: The vacuum sintered glass fiber and inorganic filler and the polyketone, anhydride grafted modified polyethylene, lubricant and antioxidant mixed, and extruded granulated to form composite particles, the extrusion temperature is 210 degrees to 240 degrees; S4: providing a substrate and copper alloy powder; S5: sintering the copper alloy powder and rolling to form a sintered layer on a substrate, wherein the sintered layer has a plurality of pores of any shape penetrating the sintered layer, and the pores account for 15-25%; S6: laying the composite particles formed in step S3 on the sintered layer, heating and rolling, and controlling the rolling temperature at 150 to 170 degrees to form the impact-resistant, wear-resistant and self-lubricating composite plate.
8. The method for preparing a composite board according to claim 7, characterized in that: After step S2 and before step S3, the method further includes the following steps: pre-treating the vacuum sintered glass fibers and inorganic fillers, that is, mixing the vacuum sintered glass fibers and inorganic fillers with an organic solvent, and drying the mixed glass fibers and inorganic fillers.
Citation Information
Patent Citations
Self-lubricating slide bearing by oil lubrication or grease lubrication
CN101413544A
Modified polyketone material, and preparation method and application thereof
CN107151438A
Long glass fiber reinforced polyketone material and preparation method thereof
CN107793739A